TEACHERS’ CHALLENGES ON TEACHING MATHEMATICS IN ENGLISH AT BILINGUAL SCHOOLS - Fitri Randia Ningsih; Ahmad Husein Nst; Aprili Yanti; Abdul Zebar; Tien Rafida (STKIP Siliwangi, 2024)
This research aimed 1) to identify the challenges faced by mathematics teachers when delivering material by using English in international school. 2) Teachers’ strategies to overcome the challenges used by the teachers to overcome these challenges; and 3) the implications of the teachers' perspective for ESP design. The study was conducted at a bilingual school in Medan that follows the Cambridge Curriculum and involved five mathematics teachers from this school. This study used Qualitative Method. Data were collected through interviews to obtain in-depth insights and an interactive analysis method was used for data analysis. The research findings reveal that mathematics teachers encounter several challenges when presenting mathematical materials in English. These challenges revolve around English proficiency, articulation, construction of the sentences and the afraid of mistake in pronunciation. In response to these challenges, teachers employ strategies to enhance their English language skills by learning from various sources, including applications, reference of books, and both printed and online materials. Additionally, they collaborate with their fellow teachers and utilize online platforms to support their learning and prepare instructional materials. These findings underscore the importance of incorporating four key aspects, namely vocabulary mastery, pronunciation, grammar proficiency, and speaking fluency, into the ESP course design for mathematics teachers.